Online Yemeni agriculture product shopping system (OYAPSS) - Alhaimi, Nabil Mohammed Ali (2019)
In today trends, Electronic Marketing is one of the so called digital economies. The digital economies are based on two facts which are the Electronic-commerce and Information Technology. Information technology in the era of computing and communication is what has created the virtual presence of Electronic-commerce, which relies mainly on computing and various means of technology for implementation and business management. The Online Yemeni Agriculture Product Shopping System (OYAPSS) website is an online system and the most important activities of OYAPSS. It is the marketing function that seeks to facilitate the exchange and flow of products from the product to the consumer through the use of specific tools and methods to achieve the benefits required by the parties to the marketing process. This process is done mainly through the Internet Based Marketing in the practice of all activities such as advertising, selling, distribution, promotion, pricing and the use of electronic methods in the process of meeting the price online. The site will serve people who do not want to shop through their travels Makes and prefer to get their products through the live images displayed on the sites dedicated to companies on the Internet. The factors of discrimination and choice will be clearer to the customers.